Association between witnessing domestic violence against the mother in childhood and intimate partner violence in adulthood: A population-based analysis of Peru - Guido Bendezu-Quispe; Daniel Fernandez-Guzman; Brenda Caira-Chuquineyra; Diego Urrunaga-Pastor; Andrea G. Cortez-Soto; Sandra S. Chavez-Malpartida; Jaime Rosales-Rimache (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2024)
Objective: To assess the association between witnessing domestic violence against the mother in childhood and intimate partner violence (IPV) in adulthood. Study design: An analytical cross-sectional study was conducted using data from the 2019 Peruvian Demographic and Family Health Survey (ENDES). The independent variable was the condition of witnessing physical violence by the father against the mother during childhood. The dependent variable was IPV, defined by the presence of some subtype of violence (physical, psychological, and sexual) against the respondent in the last year by her husband or partner. To assess this association, generalized linear models of the Poisson Family with a logarithmic link function were performed to estimate crude and adjusted prevalence ratios (aPR) with their respective 95% confidence intervals (95% CI). Results: Data from 17,911 Peruvian women between 15 and 59 years of age were analyzed. Most women were between 30 and 49 years old (71.4%), were cohabiting (65.0%), and had secondary education (43.2%). The prevalence of IPV in the last year was 16.0%, and the history of witnessing domestic violence against the mother during childhood was 42.0%. In the regression models, those with the studied exposure showed a higher prevalence of experiencing an episode of IPV in the last year (any IPV [aPR: 1.69; 95% CI: 1.50–1.91]; physical IPV [aPR: 1.70; 95% CI: 1.43–2.02], psychological IPV [aPR: 1.64; 95% CI:1.42–1.88], and sexual IPV [aPR: 1.68; 95% CI: 1.22–2.32]). Conclusions: Women with a history of domestic violence towards their mothers were likelier to have had IPV in the last year than women who did not report violence towards their mothers during childhood. Approximately two in ten Peruvian women reported having had IPV in the past year, and nearly half reported witnessing domestic violence against their mother as a child.